Detrital zircon ages of the Jiageda and Woduhe formations: Constrains on the tectonic attribute of the Xing' an terrane in the central Great Xing' an Range, NE China. (1st December 2015) - Cui, Fanghua; Zheng, Changqing; Xu, Xuechun; Yao, Wengui; Ding, Xue; Shi, Lu; Li, Juan
Highlights: Jiageda and Woduhe formations in the Great Xing' an Range are early Paleozoic strata. Jiageda Formation we studied does not constitute traditional Precambrian basement. Xing' an terrane was located in an active continental margin during early Paleozoic. Precambrian basement in NE China is not widespread and younger than Neoproterozoic. Abstract: To ascertain the late Early Paleozoic tectonic attribute of the Xing' an terrane, and the distribution and nature of the "Precambrian" basement in NE China, we studied the geochronology, petrology, and geochemistry of the metamorphic rocks of the Jiageda and Woduhe formations in the central Great Xing' an Range. U–Pb ages of detrital zircons from the Jiageda and Woduhe formations vary from 963 to 374 Ma, and can be divided into three groups (963–679, 570–468, and 457–374 Ma). The youngest detrital zircons of the three samples from the Jiageda Formation yield weighted mean ages of 413 ± 3, 414 ± 9, and 416 ± 1 Ma, respectively, indicating that this formation was formed during the late Silurian–early Devonian. The youngest detrital zircons of the sample from the Woduhe Formation yield a weighted mean age of 429 ± 4 Ma, indicating that this formation was formed during the middle–late Silurian. The protoliths of the metamorphic rocks from the Jiageda and Woduhe formations are terrigenous clastic rocks, with some mafic–intermediate volcanic rocks, characterized mainly by volcanic–sedimentary formation. Considering the geochemical characteristics of the rocks and the regional tectonic setting, we suggest that both the Woduhe and Jiageda formations were formed in an island-arc active-continental-margin environment, and that the Xing'an terrane was located in an active continental margin related to the subduction of the Paleo-Asian Ocean during the middle Silurian-early Devonian. A comparison between the Jiageda and Woduhe formations with respect to their protoliths, geochemical properties, sedimentary environment, and geochronological characteristics shows that the Jiageda Formation does not constitute Precambrian crystalline basement, but instead consists of metamorphosed and deformed late Silurian–early Devonian sedimentary strata intercalated with volcanic rocks. By combining these results with the regional geology, we conclude that the Precambrian basement in NE China is not extensively distributed, being limited to Precambrian metamorphic rocks in the northern Erguna massif and Xing' an terrane, eastern Songliao terrane, and southern Jiamusi massif, and the protolith ages are younger than Neoproterozoic.